2015
DOI: 10.1111/zoj.12341
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron analysis of a ‘mummified’ salamander (Vertebrata: Caudata) from the Eocene of Quercy, France

Abstract: An incomplete 'mummy' from the Phosphorites du Quercy (presumed Eocene) was identified as a salamander during the 19 th century. The specimen has now been computed tomography (CT) scanned, and this revealed the incomplete skeleton (with perfectly preserved bones) and soft tissues (lung). The fossil represents a new, wellcharacterized taxon. Despite the absence of the skull, several features allow a phylogenetic analysis. The fossil belongs to pseudosaurian caudates; it is tentatively assigned to the Salamandri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…This plexus comprises three nerves that emerge from the spinal cord through the spinal foramina of the last trunk vertebra, the sacral vertebra and the first caudosacral vertebra. These spinal foramina are large ( Tissier et al, 2016 : figs. 5B and 6B–6C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This plexus comprises three nerves that emerge from the spinal cord through the spinal foramina of the last trunk vertebra, the sacral vertebra and the first caudosacral vertebra. These spinal foramina are large ( Tissier et al, 2016 : figs. 5B and 6B–6C).…”
Section: Resultsmentioning
confidence: 99%
“…The study of the skeleton of Phosphotriton confirmed that this fossil is a urodele amphibian; more precisely, the phylogenetic analysis presented by Tissier et al (2016) suggested that it is a stem-salamandrid, although they did not definitely discard relationships with the Plethodontidae.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations